Development of E-LKPD Based on Project Based Learning (PJBL) on Computer Network Material - Afdhal, Muhammad Abim; Novrianti, Novrianti; Yusri, Meldi Ade Kurnia; Masnur, Alkadri (JUPE : Jurnal Pendidikan Mandala, 2025)
This research is triggered by one of the common problems encountered in Information and Communication Technology (ICT) learning, which is the low interest of students, resulting in difficulties in mastering the subject matter according to their individual learning styles. The teaching materials used have not helped students think critically, creatively, and learn independently in accordance with the demands of the Merdeka Curriculum. This study aims to produce a valid and practical e-LKPD based on Project-Based Learning for computer network material, so it can be used as teaching material for ICT. This type of research is development research (R&D) using the 4- D development model. The stages used in this development model are: Definition Stage, Design Stage, Development Stage, and Dissemination Stage. The subjects of this study are 10th-grade students from SMA Negeri X Guguak. The instruments used in the research are validity and practicality questionnaires, which are used to assess the practicality of the e-LKPD for students. The validity result of the Project-Based Learning-based e-LKPD is 90.3%, categorized as very valid. There is no final practicality score for the ICT teacher e-LKPD because there is only one ICT teacher, who serves as the material validator. The final practicality score for the student e- LKPD is 84.2%, categorized as very practical. Based on the research results, it canbe concluded that the Project-Based Learning-based e-LKPD on computer network material for 10th-grade students at SMA Negeri X Guguak is valid and practical.